A Survey on Robust Modulation Requirements for the Next Generation Personal Satellite Communications - Ssimbwa, Julius; Lim, Byungju; Lee, Ju-Hyung; Ko, Young-Chai (Frontiers in Communications and Networks, 2022)
The unrelenting technological advancement in the generation of wireless networks in recent years has awakened the motion concerning the inclusion of satellites in personal communications. Leveraging their ability to provide wide coverage, uniform services, wide bandwidth, and so forth, Satellite systems will be expected to co-exist with the current state-of-the-art infrastructure of terrestrial networks. Herein, we present a comparative study on the representative digital modulation techniques for use in personal satellite communications. We discuss the advantages and limitations of different modulation techniques, such as phase shift keying, continuous phase modulation, amplitude phase shift keying, and quadrature amplitude modulation. We also perform evaluations based on spectral efficiency, power efficiency, modulation error ratio, error vector magnitude, and peak-to-average power ratio in the presence of high power amplifier nonlinearities and Doppler effects. Comparisons in the form of tables, illustrations, and curves are also presented. In correspondence to the comparisons made basing on the aforementioned metrics, we conclude that continuous phase modulation is the best candidate modulation scheme for personal satellite communications since it outperforms other schemes by compromising the trade-off between power efficiency, bandwidth efficiency, and immunity to errors. We further present open issues that would reinforce personal satellite communications in terms of reliability, throughput and latency, other than power and spectral efficiency, if combined with appropriate modulation schemes.